PRE-ROMAN AND ROMAN BURNUM: SOME REMARKS, AND NEW EVIDENCE OF THE AUXILIARY FORT AT ČUČEVO - Nikola Cesarik (Journal of Ancient History and Archaeology)
Author discusses several subjects concerning pre-Roman and Roman Burnum (Dalmatia). Earlier authors presumed that the main centre of the Liburnian Burnistae should be located on Gradina in Puljani, a pre-Roman promontory fort located on the left bank of the river Krka. However, since Pliny the Elder mentions that river Krka forms a border between the Liburni and the Delmatae, it would be strange that the Liburnian civitas would place its centre on a promontory fort located on Delmatean side of the river. By surveying the wider landscape of the Liburnian frontier, the author argues that the centre of the Liburnian Burnistae should be located at Radučka glavica, the most dominant hillfort in the area of Kistanjska Bukovica. In the second part of the paper, the author reveals the existence of a Roman auxiliary fort at Čučevo, which is – so far – the fourth known auxiliary fort located on the right bank of the river Krka.